Africa in Milan. Three African novels in Milanese publishing in the 1950s (Altre Modernità, 2024)
The following pages investigate three novels written in English by writers from the African continent and selected by the Milanese publishing industry in the 1950s – a decade that saw the beginnings of rapidly changing editorial policies. After the end of the war, the curiosity for the exotic and the adventurous was joined – for intellectuals, publishers, and also for a growing number of readers – by the desire for an apparent discontinuity with the cultural policies of fascism; this favoured editorial experimentation and an unprecedented openness to foreign literature. The South African region stands out in the meagre panorama of books that reached the Italian market in the 1950s. From South Africa come two of the novels analysed here: Piangi, terra amata (Cry, the Beloved Country), by Alan Paton (Milano, Bompiani) and Il sentiero del Tuono (The Path of Thunder), by Peter Abrahams (Milano, Baldini & Castoldi). The third novel comes from Lesotho: Fuoco nero (Blanket Boy’s Moon), by Peter Lanham and Atwell Sidwell Mopeli-Paulus (Milano, Ugo Mursia). The analysis offered here highlights the rather daring editorial choices of the three publishing houses: they not only opened windows on distant worlds to readers unaware of the existence of African literatures, but also chose not to ‘tame’ the encounter with profoundly different cultures and languages, proposed through translations which prove very attentive to the otherness of the source culture.
Keywords: literary translation; Milanese publishers; 1950s; Africa